Oral health profile of participants of an elderly cohabitation program in the state of Santa Catarina, Brazil - Rafaela LASTA; Angélica DEVILLA; Vanessa SIMONI; Jéssica Caroline FORALOSSO; Michele Gassen KELLERMANN; Scheila MARCON; Vanessa da Silva CORRALO; Sinval Adalberto RODRIGUES-JUNIOR (Universidade Estadual Paulista, 2019)
Abstract Introduction Cohabitation and social interaction programs have been shown to enhance several aspects of the quality of life of the elderly. Objective This observational study assessed the oral health and oral health perception of participants of an elderly cohabitation program in the state of Santa Catarina, Brazil. Material and method Calibrated dental students examined/interviewed 235 participants of the program. The oral examination considered Decayed, Missing, and Filled Teeth (DMFT) index, Community Periodontal Index (CPI), Periodontal Attachment Loss (PAL), use and need of prostheses, and presence of oral mucosal lesions. Oral health perception was verified with the Geriatric Oral Health Assessment Index (GOHAI) questionnaire. Data were analyzed with descriptive statistics and chi-square test (α=0.05). Result The mean DMFT index was 24.3 teeth, with emphasis on the 'Missing' category. Upper and lower prosthetic needs were 53.6 and 71.1%, respectively. Fifty-five per cent of participants presented oral mucosal lesions. Moderate oral health perception prevailed (43%), with mean GOHAI score of 29.9. The negative perception on physical and pain/discomfort dimensions was statistically associated with lower prosthetic need (p<0.05). Conclusion The participants of the cohabitation program presented poor oral health and prevalence of moderate oral health perception. Lower prosthetic need was associated with negative perception.